OOPHORECTOMY-INDUCED BONE LOSS IS ATTENUATED IN MAGP1-DEFICIENT MICE - Craft, Clarissa S. (2012)
Microfibril-associated glycoprotein-1 (MAGP1)(¶), together with the fibrillins, are constitutive components of vertebrate microfibrils. Mice deficient in MAGP1 (MAGP1Δ) develop progressive osteopenia and reduced whole-bone strength, and have elevated numbers of osteoclasts lining the bone surface. Our previous studies suggested that the increased osteoclast population was associated with elevated levels of RANKL, a positive regulator of osteoclast differentiation. To explore the relationship between RANKL expression and osteoclast differentiation in MAGP1 deficiency, oophorectomy (OVX) was used to stimulate RANKL expression in both WT and MAGP1Δ animals. Bone loss following OVX was monitored using whole body DEXA and in vivo μCT. While WT mice exhibited significant bone loss following OVX, percent bone loss was reduced in MAGP1Δ mice. Further, serum RANKL levels rose significantly in OVX WT mice whereas there was only a modest increase in RANKL following OVX in the mutant mice due to already high baseline levels. Elevated RANKL expression was normalized when cultured MAGP1Δ osteoblasts were treated with a neutralizing antibody targeting free TGFβ. These studies provide support for increased RANKL expression associated with MAGP1 deficiency and provide a link to altered TGF-β signaling as a possible causative signaling pathway regulating RANKL expression in MAGP1Δ osteoblasts.